Inga colimana (Leguminosae) a new species from western Mexico - Padilla V., Eloy; Cuevas G., Ramón; Solís M., Arturo (Instituto de Ecología, A.C., 2005)
Inga colimana sp. nov., a species known only from the state of Colima, is described and illustrated. The plant belongs to the section Leptinga and seems to be related with I. jinicuil G. Don and I. cinnamomea Spruce ex Benth., but it differs in its smaller fruits and seeds.